Community Structure and Health Conditions of Mangrove in Sabu Raijua - Fakhrurrozi Fakhrurrozi; Zihan Yuniar; Muhammad Harun; Wiwid Andriyani Lestariningsih; Ibadur Rahman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangrove ecosystem has an important role for the coastal ecosystem in Sabu Raijua which is included in the TNP Laut Sawu conservation area. Its designation as a water conservation area indicates that the area is an important for the protection of fishery diversity and other marine resources. Mangroves play an important role for the diversity of marine biota because of their role as a breeding ground, foraging, and nursery ground for various types of marine biota. For this reason, the role of mangrove ecosystems as supporting conservation areas is very important. The functioning of the mangrove ecosystem can be seen based on the community structure and ecosystem quality conditions. This study aims to determine the condition of the community structure and health conditions of mangroves on Sabu Raijua Island. The survey location was obtained at 5 observation stations spread across Sabu Island. The results showed that 8 species of mangrove were identified with the dominance of Mangrove Lumnitzera racemosa with an IVI value of 191%. The percentage of canopy cover found ranged from 33 – 58% with an average value of 46%. Density ranges from 23 – 45 ind/plot, with an average of 31 ind/plot. The Mangrove Health Index (MHI) value in was 36.51 ± 14.05% which is included in the Moderate category. The high value of the standard deviation (14.05) indicates that there are still mangrove locations in Sabu Raijua that have poor conditions (Poor).